Quantitative PCR for parasitemia monitoring and preemptive therapy in patients with Chagas disease and autoimmune rheumatic disorders undergoing biologic treatment: a case series - Noemia Barbosa Carvalho; Vera Lucia Teixeira de Freitas; Nadia Emi Aikawa; Lucas Teixeira Vieira; Rita Cristina Bezerra; Adriana Coraccini Tonácio de Proença; Karina Bonfiglioli; Érika Yoshie Shimoda Nakanishi; Hermes Ryoiti Higashino; Maria Aparecida Shikanai-Yasuda (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Patients with chronic Chagas disease (CD) and autoimmune rheumatic disorders (ARD) receiving immunosuppressive therapy are at risk for CD reactivation (CDR). This study monitored parasitemia over 9-121 months in six patients with CD and ARD using conventional and quantitative PCR and parasitology. Five patients showed parasitemia; two had elevated levels of parEq/mL (49-458.7). One patient received benznidazole with a marked decrease in parasitemia; in the other, treatment was discontinued after 12 days due to toxicity. No CDR occurred. These findings support the need for qPCR standardization for preemptive therapy and suggest that benznidazole may prevent CDR in patients with high parasitemia.